Using of modern information framing technologies during formation of communicative competence of the future teacher of music (Pedagogy of Higher and Secondary Education, 2006)
In article features of using information framing technologies at formation of communicative competence of the future teacher of music, their version and pedagogical coalitions of introduction are considered.
Keywords: future teacher of music; modem uiformation technologies; communicative competence